2015
DOI: 10.1371/journal.pone.0135777
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anthrax Cases in North-East China, 2010-2014

Abstract: We determined the genotypes of seven Bacillus anthracis strains that were recovered from nine anthrax outbreaks in North-East China from 2010 to 2014, and two approved vaccine strains that are currently in use in China. The causes of these cases were partly due to local farmers being unaware of the presence of anthrax, and butchers with open wounds having direct contact with anthrax-contaminated meat products. The genotype of five of the seven recovered strains was A.Br.001/002 sub-lineage, which was concordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A total of 109 human anthrax cases were reported in Liaoning between 2001 and 2015. The most serious outbreak occurred in Anshan prefecture in 2011, with at least 34 human cases reported and 456 farm livestock dead or slaughtered in suffered areas [ 18 ]. At the beginning of August in 2015, one outbreak with 10 suspected cutaneous anthrax cases was reported in Xifeng County, Liaoning province, with a total of 210 people under medical observation.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 109 human anthrax cases were reported in Liaoning between 2001 and 2015. The most serious outbreak occurred in Anshan prefecture in 2011, with at least 34 human cases reported and 456 farm livestock dead or slaughtered in suffered areas [ 18 ]. At the beginning of August in 2015, one outbreak with 10 suspected cutaneous anthrax cases was reported in Xifeng County, Liaoning province, with a total of 210 people under medical observation.…”
Section: Introductionmentioning
confidence: 99%
“…Anthrax is a worldwide zoonosis, and sporadic anthrax cases have been reported occasionally in all countries of the world (16,17). Some farming regions in China are in naturally infectious areas prone to anthrax outbreaks; livestock are commonly infected by B. anthracis during farming, so many recurrent animal anthrax cases are reported (17).…”
Section: Discussionmentioning
confidence: 99%
“…Anthrax is a worldwide zoonosis, and sporadic anthrax cases have been reported occasionally in all countries of the world (16,17). Some farming regions in China are in naturally infectious areas prone to anthrax outbreaks; livestock are commonly infected by B. anthracis during farming, so many recurrent animal anthrax cases are reported (17). Guizhou Province is a historical center of anthrax in China, and sporadic human anthrax epidemics have happened frequently in Guizhou Province in recent years (9,10,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding 15 VNTR profiles described in previous studies [4, 10, 13] was also merged into the database. There was information on a total of 420 isolates in the CBaGID, including our strains ( n  = 190) and isolates from previous research ( n  = 230).…”
Section: Methodsmentioning
confidence: 99%
“…Single-nucleotide repeats (SNRs), also called mononucleotide nucleotide repeats, are a special type of variable-number tandem repeats (VNTRs) that display very high mutation rates [11, 12]. A previous study showed that seven strains of B. anthracis recovered from Northeast China from 2010–2014 were distinguished as A.Br.001/002 ( n  = 5) or A.Br.Ames ( n  = 2) sublineages, and the two A.Br.Ames strains were further identified as same SNR pattern [13]. Because SNR markers can provide additional genetic resolution among B. anthracis strains of the same MLVA genotype [14, 15], the SNR analysis has therefore been used as a means of source tracking anthrax outbreaks [14].…”
Section: Introductionmentioning
confidence: 99%